The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1083/jcb.139.7.1709
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Organization of Bovine Chromaffin Cell Cortex—Analysis by Cryofixation and Morphometry of Aspects Pertinent to Exocytosis

Abstract: We have analyzed ultrathin sections from isolated bovine chromaffin cells grown on plastic support, after fast freezing, by quantitative electron microscopy. We determined the size and intracellular distribution of dense core vesicles (DVs or chromaffin granules) and of clear vesicles (CVs). The average diameter of DVs is 356 nm, and that of CVs varies between 35–195 nm (average 90 nm). DVs appear randomly packed inside cells. When the distance of the center of DVs to the cell membrane (CM) is analyzed, DV den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 45 publications
6
144
1
Order By: Relevance
“…This mechanism may alter quantal size. However, there is little evidence for homotypic fusion in chromaffin cells at this late stage of release (52). Whether chromaffin granules aggregate during recycling or during de novo vesicle synthesis was not addressed in this study, but we did not observe multiple granules in single membrane-bound vesicles in our electronmicroscopic studies.…”
Section: Vesicle Size Is Altered In a Manner That Mirrors Quantal Sizcontrasting
confidence: 34%
“…This mechanism may alter quantal size. However, there is little evidence for homotypic fusion in chromaffin cells at this late stage of release (52). Whether chromaffin granules aggregate during recycling or during de novo vesicle synthesis was not addressed in this study, but we did not observe multiple granules in single membrane-bound vesicles in our electronmicroscopic studies.…”
Section: Vesicle Size Is Altered In a Manner That Mirrors Quantal Sizcontrasting
confidence: 34%
“…3B), colocalization of the target SNAREs on the plasma membrane is likely irrespective of vesicular proteins. This was predictable, because previous electron microscopy studies demonstrated that the vast majority of secretory granules reside away from the plasma membrane in the resting cells (16).…”
Section: Resultsmentioning
confidence: 97%
“…However, rise and decay times are not correlated with quantal size. Furthermore, the size of dense core granules rather closely follows a Gaussian distribution (Plattner et al, 1997). Therefore, these two populations of amperometric spikes probably correspond to two modes of fusion with distinct rates of fusion pore dilation and not to two groups of vesicles.…”
Section: Two Modes Of Membrane Fusionmentioning
confidence: 96%